SUBSITUSI EKSTRAK SAYUR PAKCOY PADA PEMBUATAN PUTU AYU - Rama Sari, Puja; Mandasari, Yulia; Rasyid, Rasyidin (Jurnal Pariwisata Bunda, 2023)
This research was motivated by the absence of a pastry industry that makes putu ayu cakes with the addition of pakcoy vegetable extract, therefore the author conducted research on the addition of pakcoy vegetable extracts in making putu ayu cakes, in order to obtain nutritional value for the children who consume them. The research method used is the experimental method. The data collection techniques used are documentation studies, questionnaires and literature studies. This research was assessed by panelists regarding the substitution of pak choy vegetable extract in making putu ayu cake. The results of this research show that with the addition of 50% pak choy vegetable extract, the aroma quality of the pak choy is very strong, the color quality is quite green, the quality of the sweet taste is very sweet, the quality of the pak choy tastes and tastes quite pak choy, and the quality of the softness of the putu ayu is soft. Meanwhile, with the addition of 70% pak choy vegetable extract, it can be concluded that the aroma quality of pak choy is that it smells like pak choy, the color quality is quite green, the quality of the sweet taste is sweet, the quality of the pak choy tastes pak choy, and the softness quality of the putu ayu is soft